Improvement of blown film extrusion of poly(Lactic Acid): Structure–Processing–Properties relationships. Issue 4 (24th June 2013) - Mallet, Benoit; Lamnawar, Khalid; Maazouz, Abderrahim
<x xml:space="preserve">Abstract</x> The blown extrusion of poly(lactic acid) (PLA) presents several challenges mainly due to the poor shear and elongation properties of this biopolymer. This article highlights some promising routes to enhance the processability of PLA for blown extrusion. To achieve this objective, various formulations of PLA with multifunctionalized epoxy, nucleating agents, and plasticizer were elaborated and studied on the basis of their linear viscoelasticity and elongational properties. We further characterized both the structure and thermomechanical properties of blown films produced with these PLA formulations. Stability charts for the film blowing of neat and modified PLA were thus established at different processing conditions. On the basis of these results, we managed to achieve a large enhancement of the blown processing windows of PLA with high blow‐up ratio (BUR) and take‐up ratio attained. We were able to demonstrate that a higher kinetic of crystallization can also be reached for chain‐extended and branched PLA formulated with adequate amounts of nucleating agents and plasticizers. Induced crystallization during process was also demonstrated. Through this work, blown films with interesting thermomechanical and mechanical properties have been elaborated using an optimal formulation for PLA. POLYM. ENG. SCI., 54:840–857, 2014. © 2013 Society of Plastics Engineers